Isolation of the cytotoxic constituent deoxypodophyllotoxin from the leaves of Juniperus chinensis - Kawazu, Kazuyoshi; Ismail, Intan Safinar; Takahata, Kyouya; Ali, Abdul Manaf; Kanzaki, Hiroshi (Faculty of Agriculture, Okayama University, 1997)
Deoxypodophyllotoxin was isolated as a cytotoxic constituent from ethanol extract of the leaves of Juniperus chinensis by assay-guided fractionation.